Hubungan Asupan Natrium dan Lemak dengan Tekanan Darah pada Pasien Hipertensi di Ruang Rawat Jalan Poli Penyakit Dalam Rumah Sakit Umum Daerah Bangli - Wahyuni, Komang Tri; Sugiani, Pande Putu Sri; Dewantari, Ni Made (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2024)
Hypertension is a non-communicable cardiovascular disease. The estimated incidence of hypertension in Indonesia in 2018 was 63,309,620 people, with a mortality rate of 427,218. Hypertension can be caused by excessive sodium and fat intake. The purpose was to determine the relationship between sodium and fat intake with blood pressure in hypertensive patients treated in the outpatient department of Internal Medicine at Bangli Regional General Hospital. This research applied a descriptive analytic study conducted in the Internal Medicine Polyclinic of Bangli Regional General Hospital in April-May 2024. The sample consisted of 30 individuals, using purposive sampling. The relationship between variables was analyzed by Spearman's Rank. Sodium intake showed that 18 samples (60%) were classified as good and 12 samples (40%) as excessive. Meanwhile, fat intake showed that 17 samples (56.7%) were classified as good and 13 samples (43.3%) as excessive. Blood pressure examination results showed that 13 samples (43.3%) were hypertensive, and 17 samples (56.7%) controlled blood pressure. The analysis showed a relationship between sodium intake and blood pressure (p = 0.000) and between fat intake and blood pressure (p = 0.031). Monitoring and evaluating the consumed nutrients at home and educating on diet provision for outpatient patients need enhancement.